MANAGEMENT OF THORACIC TRAUMA: EXPERIENCE AT AYUB TEACHING HOSPITAL, ABBOTTABAD. - Khan, Ishtiaq Ali; Ghaffar, Salma; Asif, Saadia; Rehman, Zia -ur-; Asad, Shawana; Ahmed, Ehtisham; Ahmed, Wasim; Asif, Zeeshan (Journal of Ayub Medical College Abbottabad, 2009)
Background: The incidence of thoracic trauma has rapidly increased in this century of high speed vehicles, violence and various other disasters. It has been observed that chest intubation was required in more than 75% of patients. Methods: This prospective study was performed in cardiothoracic surgery unit of Ayub Teaching Hospital Abbottabad from Jun 2007 to Dec 2007. A total of 114 consecutive patients with chest trauma were included in the study, their patterns of injuries classified, treatment strategies and outcome were recorded on a proforma. Results: Out of 114 patients with chest trauma, 76 (66.65%) were having penetrating and 38 (33.33%) had blunt trauma. Haemothorax was detected in 67 (58.77%), Pneumothorax in 23 (20.17%), rib fracture in 11 (15.02%) and diaphragmatic injuries in 4 (3.5%) cases. Overall complication rate was 14%. Wound infection was present in 8 (7.01%) and empyema in 4 (3.5%). Mortality was 2.6%. Conclusion: Penetrating chest injuries were more common than blunt injuries and chest intubation with resuscitation was adequate in most of the patients. Keywords: Chest Trauma, Penetrating chest injuries, chest intubation.